An Extensive Study of Digital Image Steganography Techniques - Singh, Juhi; Singla, Mukesh (Indian Journal of Computer Science, 2022)
The rise of digital technology raises the importance of data security when transmitting data across a wireless communication medium. Steganography is a method of ensuring information security on a digital media. The goal of this work is to look at information hiding techniques in images which are in the spatial domain. This paper will also distinguish between watermarking and steganography, the two most popular domains of information concealment. The paper examines the benefits and drawbacks of existing algorithms, tools, and strategies to safeguard data in the digital image steganography domain.